A CASE STUDY: NEUTRALITY POSTURE OF THE MEDIATOR IN INTERCULTURAL MEDIATION - Poloogadoo, Raginee (Lex Electronica)

(untitled) (Centre de recherche en droit public Université de Montréal, 2023)
Mediation is becoming a more peaceful and internationally accepted solution for solving conflicts. It is a dynamic and interactive process where a neutral third party that is the mediator assists disputing parties in resolving conflict. Normally, there is an assumption that the mediator will remain neutral. This thesis explores the neutral posture of the mediator when dealing with inter-cultural mediation. The purpose of this qualitative study was to investigate the understanding and implementation of neutrality of the intercultural mediator in practice. The research questions focused on the mediator’s perceptions, interpretations, conceptions, implementation and effectiveness of the neutrality posture at mediation. Ten face-to-face semi-structured interviews were conducted with intercultural mediators hailing from diverse geographical locations. Data were coded and analyzed through thematic analysis. The findings of the study revealed that intercultural mediators have different views of neutrality in mediation. Moreover, they adopt the meaning and posture of neutrality according to their self-determination in practice. An alternative discourse for this study should be to frame a standard meaning to the term of neutrality by giving its absolute significance in mediation.